A methodology for smart grid reconfiguration - Bento, Fábio Ricardo de Oliveira; Celeste, Wanderley Cardoso (Latin American Journal of Energy Research, 2021)
In this work, it is presented a methodology for the reconfiguration of smart grids that is applied to a smart grid formed by two microgrids that can be electrically interconnected in contingency situations. Each microgrid is also connected to an Electric Power System (EPS) when operating in the normal state. Moreover, the smart grid includes energy storage devices (batteries) located at strategic points. Serious faults that isolated the microgrids of the EPS and, moreover, considerably reduced the generation capacity of such microgrids are simulated. The proposed methodology is applied to reconfiguration in scenarios involving cooperation between microgrids and/or the use of energy storage devices. Performance indices are also proposed to enable a quantitative analysis for each scenario. It is shown that intelligent cooperation between microgrids and the smart-use storage energy is the best option for reducing the impacts in a contingency scenarios.